# Distributive property-Subtraction

by C0nfused
Tags: distributive, propertysubtraction
 P: 136 Hi everybody, 1) We have defined the distributive propery of multiplication like this: a(b+c)=ab+ac and (a+b)c=ac+bc . So when we have (a+b)(c+d) , how do we get the result using the above definition? We just consider one of the parentheses as one number so we get (a+b)c+(a+b)d for example(we think of (a+b) as a number g?)? 2) And one more thing: we define -x as the number that when added to x gives a sum 0. We also define that -x=(-1)x and a-b=a+(-b) (definition od subtraction). So when we have an expression like this: a-b-c+d-e this is considered a sum ? I mean the minus signs in the above expression show subtraction or the above is the same (i mean not only in the result but also in the interpretation of it) as this: a+(-b)+(-c)+d+(-e) ? The 1st refers to multiplication of reals or generally for scalar multiplication in a vector space or multiplication in a field The 2nd refers to reals but also generally to addition in a vector space They may be silly questions but i like to understand things by using only the definitions Thanks
 PF Patron HW Helper Sci Advisor Thanks P: 11,935 You're right about 1) As for 2) We do NOT define -x=(-1)*x, we prove that statement as follows: a) For any real number "a", we have a*0=0 PROOF: z=a*0=a*(0+0)=a*0+a*0=z+z, that is: z=z+z But, since "z" is a real number, it has an additive inverse -z: z+(-z)=z+z+(-z) which means 0=z. which was what we should prove. b) The additive inverse of a number is unique: Proof: Suppose z2 was an additive inverse to z other than (-z). Then: 0=z+z2, adding (-z) to both sides yields: (-z)=z2 c) Since x=1*x, we have: x+(-1)*x=x*1+x*(-1)=x*(1+(-1))=x*0=0, by a). Bot from b), it then follows that (-1)*x=(-x)
 P: 136 Thanks for your answer. I think that one part was not answered: "So when we have an expression like this: a-b-c+d-e this is considered a sum ? I mean the minus signs in the above expression show subtraction or the above is the same (i mean not only in the result but also in the interpretation of it) as this: a+(-b)+(-c)+d+(-e) ?"
PF Patron
HW Helper